Evolutionary game analysis of coal industry chain supply chain risk prevention and control from the perspective of resilience - Ziming Zhang; Xinping Wang (Sustainable Futures)
Promoting transformation of energy structure while preventing industry chain supply chain risks has become an important issue facing coal industry chain supply chain (CICSC) under “carbon peaking and carbon neutrality”. This study is based on evolutionary game model to investigate the risk prevention and regulatory issues involving chain master enterprises, other enterprises, and government regulators. Research results indicate that: (1) System evolution of risk prevention and control of CICSC is not constant convergence in theoretical optimal strategy combination, there is a systematic bias in behavioral decision-making. (2) Reference effect, risk preferences and other subjective preferences heterogeneity affects value judgment of decision makers. The effect of cost reference is greater than that of utility reference, maintaining risk avoidance in cost problems and risk pursuit in revenue problems can help to improve the quality of individual decision-making. (3) There is a non-linear effect of fairness preference on risk prevention and control of CICSC, it makes fairness preference have the positive impact to risk prevention and control when intensity of fairness preference is in moderate range and types of fairness preference are arranged and combined in a scientific order, otherwise, fairness preference will become a kind of behavior that is “detrimental to others and not beneficial to oneself”. We propose new insights for risk prevention and control from the aspects of achievement transformation and guarantee mechanisms, building reward and punishment mechanisms and so on, call for further analysis of risk prevention and control according to specific risks in each link of CICSC in future research.